Screening For Small Molecule Inhibitors Of HIV-1 VPR: Discovery Of Vipirinin And Its Use As A Bioprobe - Ong , Eugene Boon Beng (2011)

(untitled)
The human immunodeficiency virus 1 (HIV-1) viral protein R (Vpr) is an accessory protein that has been known to have multiple roles in HIV-1 pathogenesis. Here, a high-throughput screening (HTS) system was developed to screen chemical libraries in RIKEN Natural Products Depository (NPDepo). Through HTS, NPD4456, a 3-phenyl coumarin based compound, was identified to be an inhibitor of the cell cycle arrest activity of Vpr in yeast. The minimal pharmacophore of the inhibitor was determined through a structure-activity relationship study and more potent derivatives were produced.